Reconstruction of the Tongue after Hemiglossectomy Using Serratus Anterior Muscle Free Flap - Šín, Petr; Hokynková, Alica; Rotschein, Pavel; Pejčoch, Radek; Nártová, Lucie (Case reports in otolaryngology, 2023)
BACKGROUND: Serratus anterior muscle free flap is widely used in numerous indicated reconstructions. Only a few studies have dealt with the use of this flap in tongue reconstruction. MATERIALS AND METHODS: We present a case series of 7 patients with carcinoma of the tongue who underwent hemiglossectomy followed by immediate reconstruction with serratus anterior muscle free flap between January 2017 and December 2019 at the University Hospital Brno. The aim of this study was to evaluate safety and efficiency of the reconstruction as well as the donor site morbidity. RESULTS: There was not a single case of flap failure observed and the donor site healed completely in all cases. The functional outcome (tongue mobility, phonation, and deglutition) depended on the severity of the primary oncological disease and health status of the patient. CONCLUSION: The serratus anterior muscle free flap represents an alternative option for reconstruction of the tongue.